MEKANISME PENENTUAN NILAI APPRAISAL DAN PENGIKATAN HAK CIPTA SEBAGAI OBJEK JAMINAN FIDUSIA - Reni Budi Setianingrum (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
Act number 28 of 2014 on Copyright regulates that the Copyright as a movable intangible objects can be used as fiduciary transfer of ownership. Provisions regarding Copyright as the object of fiduciary transfer of oiwnership will be implemented in accordance with the provisions of the legislation applied. But practically, it is still being debated, both from the holders of copyright, as well as banks and Notaries as the official maker of the Deed of Fiduciary because there is no implementing regulations are clear, so recently there is no party that provides credit with collateral in the form Copyright. This research aims to study the binding mechanism of Copyright as fiduciary transfer of ownership’s object in lending in terms of readiness of the Appraisal authority to determine the economic value of the collateral. This type of research is normative juridical research.